TAZKIYAT AL NAFS SEBAGAI UPAYA DALAM MEMBENTUK AKHLAK SISWA MBI AMANATUL UMMAH MOJOKERTO - Ali Ahmad Yenuri (Institut Keislaman Abdullah Faqih Gresik, 2019)
Abstract: Tazkiyat al nafs is a form and method in order to cleanse the soul into a clean soul, with a clean soul it will give birth and reveal in his life a good morals because the process of tazkiyat al nafs is a step in shaping the character which is done by starting from oneself. First, the forms of tazkiyat al nafs which are done by students at MBI Amantul Ummah, there are two categories, the first is tazkiyat al nafs which is required or becomes an MBI policy which includes, prayer, fasting, zakat and infaq, reading the Koran and remembrance while that is not required but also carried out by each MBI student is tafakur, remembering death, tawadhu 'amar ma'ruf nahi munkar. Secondly, in the implementation of the tazkiyat al nafs the MBI students Amanatul Ummah have carried out in accordance with the correct procedures namely to be serious and carry out in accordance with the procedures of each form and process of implementation, so that in carrying out all of them are able to provide results that are maximal in the process of tazkiyat al nafs, Third, the role of tazkiyat al nafs in the formation of morals is as motivation in life, role as a way of life, role as doctrine and role as a reference in life so that human beings are truly spiritually and have good noble character, both towards God himself and humans around. Keyword: Tazkiyat al Nafs, Doktrin, Akhlak